1996
DOI: 10.1097/00005053-199608000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parental Communication Deviance and Relapse in Schizophrenic Patients in the 1-Year Period After Hospital Discharge

Abstract: The present pilot study examined the ability of parental communication deviance (CD) to predict relapse in schizophrenic patients in the 1-year period after hospital discharge. Measures of CD were obtained from verbatim transcripts of family problem-solving discussions for 20 schizophrenic patients and their parents at an initial assessment and before the patients' hospital discharge. Relapse was assessed using the Brief Psychiatric Rating Scale at 3-month intervals after discharge. Findings indicated that par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…CD scores were calculated as the number of instances of CD divided by the number of words spoken to account for verbosity (as recommended by previous researchers; Hirsch & Leff, 1971; Miklowitz & Stackman, 1992). This coding protocol has been shown to have good reliability and construct validity (Velligan et al, 1990), and has been previously used with clinical (Velligan, Funderburg, Giesecke, & Alexander, 1995; Velligan et al, 1996) and high-risk populations (Velligan et al, 1988). The system has also been previously applied to 5-min speech samples (Kymalainen, 2005; Kymalainen, Weisman, Rosales, & Armesto, 2006), and to natural speech samples (Docherty, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…CD scores were calculated as the number of instances of CD divided by the number of words spoken to account for verbosity (as recommended by previous researchers; Hirsch & Leff, 1971; Miklowitz & Stackman, 1992). This coding protocol has been shown to have good reliability and construct validity (Velligan et al, 1990), and has been previously used with clinical (Velligan, Funderburg, Giesecke, & Alexander, 1995; Velligan et al, 1996) and high-risk populations (Velligan et al, 1988). The system has also been previously applied to 5-min speech samples (Kymalainen, 2005; Kymalainen, Weisman, Rosales, & Armesto, 2006), and to natural speech samples (Docherty, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Difficulties with language have also been documented in studies of communication deviance, which have found unclear, amorphous, disruptive, or fragmented communication among the parents of schizophrenia patients (Wynne and Singer 1963 b ; Singer and Wynne 1965; Doane et al 1981; Rund 1986; Velligan et al 1990; Docherty 1993; Docherty 1994; Miklowitz 1994; Rund 1994; Velligan et al 1995; Docherty et al 1996; Velligan et al 1996). Given these communication problems, it is not surprising that relatives of schizophrenia patients also show signs of thought disorder (Lidz et al 1962; Wynne and Singer 1963 a ; Wynne and Singer 1963 b ; Rosman et al 1964; Singer and Wynne 1965; Schopler and Loftin 1969; Arboleda and Holzman 1985; Saccuzzo et al 1988; McConaghy 1989; Shenton et al 1989; Romney 1990).…”
Section: Clinical Features Of Schizotaxiamentioning
confidence: 96%
“…This coding protocol has been shown to have good reliability and construct validity (Velligan, Goldstein, Nuechterlein, Miklowitz, & Ranlett, 1990) and has been previously used with clinical (Velligan et al, 1996;Velligan, Funderburg, Giesecke, & Alexander, 1995) and highrisk populations (Velligan et al, 1988). The system has also been previously applied to natural speech samples (Docherty, 1993) and to FMSS (Kymalainen, 2005;Kymalainen, Weisman, Rosales, & Armesto, 2006).…”
Section: CDmentioning
confidence: 99%